QATH’Y DAN ZHANNY DALAM HUKUM KEWARISAN ISLAM: (ANALISIS MAQASID SYARI’AH TERHADAP SISTEM PEMBAGIAN WARISAN) - Subeitan, Syahrul Mubarak; Muthahhar, Ahmad (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2020)
Qath’y and zhanny are a theory in language about a show the text to know the clarity and disguise of the text to a meaning. Qath’y and zhanny in Ushul Fikih used to explain the text of the source of Islamic law in al-Qur’an and Hadis in two things, al-Tsubut (existence) or al-Wurud (sourced from the truth) and ad-Dalalah (interpretation). This article will explain the differences of ulama in two concepts (qath’y and zhanny) is about inheritance law texts. After that, the concept will analyze by Maqasid al-Syari’ah approach. The result from the analysis that the texts of Islamic Inheritance Law is categorize as zhanny ad-Dalalah. The texts that deal with social society (muamalah) has influenced by social-economic in community. So that, creating the consequences of a religious text is about inheritance law to open the modern interpretation.